Solid modeling of machining centre SVM1F4 in KOMPAS 3D - Кроль, Олег Семенович; Сухорутченко, Иван Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
A three-dimensional solid model of a special-purpose mill-drill-bore machine VM1F4 with CNC in CAD KOMPAS-3D was developed. A study of the design performance by strength and stiffness criteria using the finite element method within an APM FEM module, integrated into the KOMPAS-3D system was carried out. A three-dimensional model of the turntable of the considered machine using the original embodiment of sliding supports and anti-backlash worm gear was presented. The need for such works is caused by, on the one hand, the requirements of an integrated approach to creating competitive machine tools, including the construction of a three-dimensional representation of complex design and optimization of the product according to the metal intensity and stiffness criteria. On the other hand, the implementation of an integrated approach is reasonable to carry out using low-cost CAD, which corresponds to the financial capabilities of small and medium-sized design divisions. Version of an integrated CAD KOMPAS-3D with integrated SAE - ARM FEM module is the most appropriate. As a result of investigations, the rational structure and shape of the machine complex that includes machine spindle positioning device and turntable device with a vertical and a horizontal axis for implementing complex shaping movements was determined. A new approach to improving the accuracy of dividing movements of the turntable due to using a new method of clearance compensation in the worm gear was proposed. The obtained results allow to outline the ways to improve the design, by determining dangerous sections and implementing a version of the spindle, approximated to full-strength part. In conditions of the long operation, the option of maintaining the accuracy characteristics of manufactured products by reducing the errors of dividing movements of the turntable of the machine with the workpiece mounted thereon was proposed.